A revised chronology for the growth and demise of Loch Lomond Readvance ('Younger Dryas') ice lobes in the Lochaber area, Scotland. (15th November 2020) - Palmer, A.P.; Matthews, I.P.; Lowe, J.J.; MacLeod, A.; Grant, R.
Abstract: We present a revised varve chronology for the duration of ice-dammed lakes that formed in the Lochaber district, Scotland, during the Loch Lomond ('Younger Dryas') Stadial. We analysed new varved sequences and combined them with existing varve records to develop the Lochaber Master Varve Chronology 2019 (LMVC19), published here for the first time. It spans an interval of 518 ± 18 vyrs and is considered more secure than its predecessors because: (i) it is anchored by a more robust record of the Vedde Ash, which is dated to 12, 043 ± 43 cal yr BP; and (ii) it provides revised estimates of the timings of key regional palaeoclimatic shifts that are fully compatible with those inferred from independently-dated, non-varved records obtained from neighbouring sites. The new results indicate that the Lochaber ice-dammed lakes existed between ∼12, 135 and 11, 618 ± 61 cal yr BP, but the pattern of glacier advance that led to lake formation was more complex than previously assumed, with some ice fronts reaching their maximal positions 300 years before others. Initiation of ice retreat at ∼11, 800 cal yr BP appears to have coincided with a rise of ∼2 °C in mean July temperatures inferred from chironomid data obtained from the Abernethy Forest site in the eastern Highlands. This local climatic shift is thought to have been a delayed response (by up to 335 years) to a mid-Stadial northward migration of the North Atlantic Polar Front, the delay probably due to the influence of the SW Highland icefield. Subsequent retreat that led to the formation of ice stagnation features throughout large parts of the area was initiated by a further rise in summer air temperature of ∼3 °C at the start of the Early Holocene. Final drainage of the lake system occurred ∼190 years after the initiation of ice retreat, while it took a further 200 years for the ice to vacate the Rannoch plateau, a nearby upland glacial source. Highlights: A revised glaciolacustrine varve chronology linked to the Parallel Roads of Glen Roy show the lakes existed for 518 ± 18 years. LMVC19 is tied to an absolute timescale using the Vedde Ash for the first time at a UK site and dating the lakes to between 12, 135 and 11, 618 ± 61 cal yrs BP. The two main ice lobes reached their maxima in the later Loch Lomond Stadial asynchronously by up to 300 yrs. Ice retreat began ∼11.8 cal ka BP with lake lake drainage occurring within 200 years and near complete loss of the SW Highland Icefield within ∼350 years. A change in climatic conditions in the Lochaber record dated to ∼11.8 cal ka BP is synchronous with a rise in July temperatures in Scotland but appears delayed in comparison to other NW Europe records.